2015
DOI: 10.3389/fnsys.2015.00058
|View full text |Cite
|
Sign up to set email alerts
|

Systems approach to the study of brain damage in the very preterm newborn

Abstract: Background: A systems approach to the study of brain damage in very preterm newborns has been lacking.Methods: In this perspective piece, we offer encephalopathy of prematurity as an example of the complexity and interrelatedness of brain-damaging molecular processes that can be initiated inflammatory phenomena.Results: Using three transcription factors, nuclear factor-kappa B (NF-κB), Notch-1, and nuclear factor erythroid 2 related factor 2 (NRF2), we show the inter-connectedness of signaling pathways activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 239 publications
0
22
0
1
Order By: Relevance
“…It has been shown that bacterial plasmid DNA activates a signaling cascade that leads to activation of the NF-κB pathway and expression of inflammatory genes [ 31 ]. There is also accumulating evidence that NF-κB activity increases with the onset of labour [ 32 , 33 ] and is tied to children’s health later in life [ 34 ]. Of the five NF-κB genes that were differentially methylated, four are known to induce NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that bacterial plasmid DNA activates a signaling cascade that leads to activation of the NF-κB pathway and expression of inflammatory genes [ 31 ]. There is also accumulating evidence that NF-κB activity increases with the onset of labour [ 32 , 33 ] and is tied to children’s health later in life [ 34 ]. Of the five NF-κB genes that were differentially methylated, four are known to induce NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale starts from the well-established, intimate structurefunction link where rapid structural maturation of brain circuitry is guided and driven by endogenous neuronal activity (Vanhatalo and Kaila, 2006;Hanganu-Opatz, 2010;Luhmann et al, 2016;Keunen et al, 2017;Khazipov and Milh, 2018). There is also an increasing awareness of the sensitivity of early neuronal network activity to a variety of stress factors ranging from metabolic imbalance, such as nutritional stress, medical adversities and medical treatments (Keunen et al, 2015;Leviton et al, 2015;Videman et al, 2016Videman et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Ó÷èòûâàÿ ïðîâîñïàëèòåëüíûé ýôôåêò NF-kB, ýòîò ñèãíàëüíûé ïóòü ìîaeíî ðàññìàòðèâàòü êàê ìèøåíü äëÿ ðåãóëÿöèè ïðîíèöàåìîñòè ÃÝÁ [44]. Äîêàçàíî, ÷òî àêòèâàöèÿ NF-kB ïðîèñõîäèò íå òîëüêî ïîä âëèÿíèåì HIF-1 â óñ-ëîâèÿõ ãèïîêñèè, íî è ïðè äåéñòâèè ëèïîïîëèñàõàðè-äîâ.…”
Section: ìîëåêóëû Hif-1-àññîöèèðîâàííûõ ñèãíàëüíûõ ïóòåéunclassified